Menyeimbangkan Kewajiban Global dan Kepentingan Nasional: Dampak Perjanjian TRIPs Terhadap Kebijakan Hak Paten di Indonesia - Christine S. T. Kansil; Juan Joubert Immanuel Panelewen (CV Rewang Rencang, 2024)
This research exploes the role of Intellectual Property Rights (IPR) in driving innovation and economic development in Indonesia, as well as the callenges faced in its implementaion. The primary focus of this study is the impact of the implementation of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement on Indonesia's IPR regulations, particulaly patents. This study employs a qualitative approach utilizing the normative juridical method. The study identfies regulatory changes resulting from Indonesia’s ratification of TRIPS, such as the 20-year patent protection period, and the challenges faced by the pharmaceutical industry, such as high drug prices influenced by patents. To address this, the Indonesian government has utilized compulsory licensing policies to improve access to essental medicines. The research also examines efforts to protect Indonesia’s traditional cultura heritage, which is vulnerable to exploitation by foreign parties, as exemplified by the “batik Malaysia” case. Measues taken by the Indonsian government, including strengthening law enforcement and providing incentives for local innovation, are also analyzed in this context.